Effects of different levels of artificial defoliation on the vegetative and reproductive stages of soybean - Fernandes, Eires Tosta (2022)
Any factor that may limit the leaf area of the crop in soybean may compromise its development and, consequently, its productivity. The aim of the study was to evaluate the effect of different levels of artificial defoliation performed in the vegetative and reproductive stages of two soybean cultivars, FT Campo Mourão and Brasmax Potência. The treatments consisted in: 1) Without defoliation throughout the culture cycle; 2) 16.7% defoliation in the vegetative stage; 3) 33.3% on vegetative stage; 4) 16.7% on reproductive stage; 5) 33.3% on reproductive stage; 6) 16.7% throughout the soybean cycle; 7) 33.3% defoliation throughout the soybean cycle. Regardless of the level of defoliation performed on soybeans, it was found that the cultivar Brasmax Potência presented the higher values of plant height, number of pods/plant and green weight of the aerial part, when compared to cultivar FT Campo Mourão. However, the number of pods/plant, green weight of the areal part, grain yield and weight of the seeds were not influenced by the defoliation intensities applied to the soybean. Based on the results, the threshold level of 30% of defoliation in the vegetative stage or 15% in the reproductive stage of soybean is still considered valid for the control of defoliating caterpillars in soybean crop.